Preparation and Composition of Arabic Language Materials for Non-native Speakers of Arabic (A Comment on the Preparation of Arabic Language materials at the Center of Language Development at Antasari Islamic state University) - Muradi, Ahmad (Tarbiyah : Jurnal Ilmiah Kependidikan, 2017)
The preparation of educational materials is conducted to several principles, since it is based on psychological, cultural, educational and linguistic aspects. In preparing Arabic language materials, non-native speakers of Arabic have to take into account the local aspect such as the conditions and situations that surrounding them as well as their ability to draw them closer into their life’s experiences. This can accelerate leaners to understand the Arabic language through educational materials prepared during their study of Arabic.